Integrating Science, Technology, and the Arts within Educational Psychology to Foster Creativity, Innovation, and Collaboration among Prospective Christian Education Teachers - Lidiawati Lidiawati; Stephanus Alfa; Donalia Reynaldo (International Forum of Researchers and Lecturers, 2025)
This study explores the integration of Science, Technology, and the Arts (IPTEKS) within an educational psychology framework to support the development of creativity, innovation, and collaboration among prospective Christian religious education teachers in West Java. Using a mixed-methods approach with a sequential explanatory design, the research combines quantitative and qualitative perspectives to obtain a comprehensive understanding of the phenomenon. Quantitative data were gathered through questionnaires distributed to prospective teachers, while qualitative data were obtained through in-depth interviews and participatory observations involving selected informants. The findings indicate that meaningful integration of IPTEKS contributes positively to the development of creative thinking, innovative teaching practices, and collaborative learning skills. Qualitative insights further reveal that institutional support, continuous professional development, and contextualized learning environments play a crucial role in optimizing the impact of IPTEKS integration. The study highlights the importance of aligning technological integration with psychological and pedagogical principles. It concludes that teacher education programs need to redesign curricula and training models that holistically integrate IPTEKS and educational psychology to foster relevant, transformative, and value-based learning in Christian education contexts.